From the history of the change of oikonyms in Linkmenys Parish: *Tikminaĩ / *Tikmenaĩ → Rukšėnaĩ - Bilkis, Laimutis (Baltistica, 2024)
This article examines a case of change in the names of the village Rukšėnai, which is situated in the present-day territory of Ignalina District Municipality and was previously part of the historical Linkmenys parish. Historical sources reveal that from the 16th to the mid-18th century, the village was known by a different name: Sioło Thykńińskie, sioła Thykninskiego, Sioło Thykmiskiego, sioła Thyknienskiego, sioła Tykninskiego, Sioło Tÿkmianskie, Siołem Tykmianskim, Tykmiány, de Tikmiany, Wies Tykmiany, etc. This oikonym was still known to the old residents of Rukšėnai in the first half of the 20th century. Taking into account the peculiarities and tendencies found in recordings of historical Lithuanian place names in other languages, two possible Lithuanian forms, i.e. *Tikminaĩ / *Tikmenaĩ, are reconstructed. The hypothesis proposed is that these forms originated from the compound personal names *Tik-minas / *Tik-menas. I emphasize that such personal names were not known previously in Lithuanian anthroponymy.